Implementation of Islanding Recognizing Technique for Wind Distributed Generations Considering Insignificant NDZ - Raza, Safdar; Munir, Hafiz Mudassir; Shafique, Nouman; Amjad, Wajiha; Bajaj, Mohit; Alghaythi, Mamdouh L. (Frontiers in Energy Research, 2022)
The incorporation of distributed energy resources (DERs) into the electricity grid yields environmental, technical, and economic benefits. However, in addition to the benefits, the widespread use of DERs causes technical issues. Islanding is a big concern in terms of equipment protection and personnel safety, and it should be detected as soon as possible. The proposed approach employs a passive islanding detection technique based on reactive power (Q). The Q was chosen following a comparison of five other indices. Comparative analysis reveals that Q has the highest sensitivity and accuracy for islanding recognition when compared to all other observed parameters. Different case studies have been performed considering the worst-case scenarios to check the working efficiency of the proposed scheme that simply distinguishes the islanding conditions from non-islanding conditions, which include load, motor and capacitor switching, various types of fault switching, DG tripping cases, and weak grid contribution. The proposed strategy is straightforward, with quick execution and simple implementation in the MATLAB/SIMULINK environment on the IEEE 1547-2018 generic test system. With a small non-detection zone, islanding is detected in 0.038s.